HUBUNGAN ANTARA MOTIVASI KERJA DAN KEPUASAN KERJA DENGAN KINERJA GURU DI SMK NEGERI SE KECAMATAN RAMBAH KABUPATEN ROKAN HULU - FITRIA FITRIA; HASNAH FAIZAH; AZHAR AZHAR (Universitas Riau, 2017)
The purpose of this study is to reveal the relationship between work motivationand job satisfaction with the Teacher Performance in SMK Sub-District of Rambah RokanHulu, this research used survey method with techniques korelasinonal, The variables consistedof two independent variables that work motivation (X1) and job satisfaction (X2) while thedependent variable is the Teacher performance (Y). Research shows that that the correlationcoefficient between work motivation (X1) with the performance of teachers (Y), obtained theregression equation is Û = 22 698 + 0,752X1 of this equation can be interpreted that eachincrease of one unit of work motivation (X1) will be followed by the increase in performanceteacher of 0.752 at a constant 22 698 teachers SMK sub-district Rambah Rokan Hulu, thestatistical results showed that motivation contributes very significantly to the performance ofteachers of SMK Negeri sub-district Rambah Rokan Hulu, for the correlation coefficient betweenjob satisfaction ( X2) with the performance of teachers (Y), obtained the regression equation isÛ = 18 702 + 0,800X2 of this equation can be interpreted that each increase of one unit of jobsatisfaction (X2) will be followed by a rise of 0,800 on the performance of teachers in theteacher’s constant SMK Negeri 18 702 Sub-District Rambah Rokan Hulu, the statistical resultsshowed that job satisfaction contributes very significantly to the performance of teachers ofSMK Negeri Rambah sub-district of Rokan Hulu, As for the multiple regression test betweenmotivation and job satisfaction with the performance of a teacher SMK Rokan Hulu subdistrictRambah can be seen in the regression equation is as follows Û = 15 212 + 0,328X1 + 0,515X2.The statistical results showed that motivation and job satisfaction on a constant 15 212 contributedto improving teacher performance of 0.328 and 0.515 at SMK teachers Rambah sub-district ofRokan Hulu.